1997
DOI: 10.3109/10799899709036595
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of α-Melanotropin and Agouti on B16 Melanoma Cells: Evidence for Inverse Agonism of Agouti

Abstract: alpha-Melanocyte-stimulating hormone (alpha-MSH, alpha-melanotropin) and agouti control the switch between eumelanin and pheomelanin synthesis in mammalian melanocytes. Here we investigated interactions between alpha-MSH, agouti protein, cAMP elevating agents and phorbol ester on mouse B16 melanoma cells. Agouti (Kd 3.7 nmol/l) and alpha-MSH (Kd 2.3 nmol/l) had similar affinities to the MC1 melanocortin receptor. Both alpha-MSH and agouti induced MC1 receptor down-regulation. Agouti antagonized melanogenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 40 publications
4
52
1
Order By: Relevance
“…Structures of hMC4R small-molecule agonists. Putative arrangement of the N-terminal fragment (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) inside the binding pocket of hMC4R, docked similarly to the peptide agonistα-MSH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The N-terminal fragment is shown in the licorice representation colored by element,α-MSH is shown by a thin purple line.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Structures of hMC4R small-molecule agonists. Putative arrangement of the N-terminal fragment (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) inside the binding pocket of hMC4R, docked similarly to the peptide agonistα-MSH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The N-terminal fragment is shown in the licorice representation colored by element,α-MSH is shown by a thin purple line.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…We and others hypothesize that keratinocyte-derived α-MSH binds to Mc1r on epidermal melanocytes, initiating downstream production of the cAMP second messenger through activation of adenylyl cyclase 1 . Eumelanin synthesis can be stimulated pharmacologically by agents that raise cAMP levels 1,14,[31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that both AP and AgRP act as inverse agonists rather than classical competitive antagonists of MCRs (9). Thus, these authors (8,9) suggest a more complex mechanism by which APs and the melanocortin peptides mediate a physiological response via the MCRs.…”
Section: Introductionmentioning
confidence: 99%